EXPLORING THE RELATIONSHIP BETWEEN ATTACHMENT STYLES AND ADULT ROMANTIC RELATIONSHIPS - Sumaira Malik (Global Journal of Multidisciplinary and Applied Sciences, 2024)
Attachment theory, initially developed by Bowlby (1969), posits that early bonds between children and their caregivers significantly influence the development of attachment styles that affect adult relationships. This study investigates how different attachment styles—secure, anxious, avoidant, and disorganized—shape romantic relationships in adulthood. Using a mixed-methods approach, including surveys and in-depth interviews, we examine the impact of attachment styles on relationship satisfaction, communication patterns, and conflict resolution. The study finds that individuals with secure attachment styles report higher levels of relationship satisfaction and healthier communication, while those with anxious or avoidant attachment styles struggle with emotional regulation and intimacy. The article discusses the implications of these findings for relationship counseling and offers recommendations for enhancing relationship stability through therapeutic interventions.